Towards environmental sustainability: further evidences from decarbonization projects in Kenya’s Blue Economy - Rasowo, Joseph Ouma; Nyonje, Betty; Olendi, Robert; Orina, Paul; Odongo, Salome (Frontiers in Marine Science, 2024)
Kenya is contributing towards committed to the global efforts on climate change mitigation and adaptation to climate change through investments as seen through investments in various sustainable green as well as and blue economy projects. In this review paper, we present the current status of what has been done, particularly on the blue carbon offset initiatives being undertaken undertaken in the mangrove and seaweed ecosystems as well as the decarbonization activities towards greening at the port Kenya's ports of Mombasa and which should form reference information for local, regional, bilateral/multilateral partners, scientists and other climate change stakeholders. The blue carbon offset projects involve mangrove conservation, reforestation and carbon credit sale as well as seaweed farming. The initiatives have several unique features amongst which are the community-led income generation systems that simultaneously act as an inducement for ecosystem preservation, comanagement and benefits sharing which are recipes for economic, socio-cultural, and environmental sustainability. A notable Notable project impact s include is the conferment of economic power to the locals, particularly the women and the youth, whose livelihoods would otherwise depend solely on their husbands. The model used embraces a collaborative approach involving multisectoral engagements of both the government, multilateral organizations, NGOs, and local communities. This integrated top-down (government) and bottom-up (local community) method deliberately targets the strengthening of economic development while ensuring sustainability. This review further reports on the several initiatives being undertaken to decarbonize the Port of Mombasa.